In-service teachers’ training needs in implementing life skills education in rural secondary schools in Lesotho - Nthofela Tsiu (International Journal of Studies in Psychology)
The teachers’ preparation in teaching and learning Life Skills Education is crucial in the education system in Lesotho. This study explores the teachers’ training needs in implementing Life Skills Education at rural secondary schools in Lesotho. The study adopted qualitative interpretivism and phenomenological research design. Eight LSE teachers and principals were chosen randomly from four schools. Telephonic semi-structured interviews were used for data collection. The thematic results revealed that teachers were not trained to teach LSE and needed in-service courses. The findings yielded that the teaching and learning of LSE must be enhanced in secondary schools. Thus, it recommended that the Ministry of Education facilitate and broaden in-service training of LSE teachers and provide a framework for guiding the contents of LSE. The curriculum developers would find the research helpful as they reflect on the extent to which the objectives were achieved for the subject.